2012
DOI: 10.5005/jp-journals-10024-1166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citric Acid and EDTA on Periodontally Involved Root Surfaces: A SEM Study

Abstract: Aim: Root debridement by scaling and root planing may not completely remove contaminated cementum particularly in more apical areas. The smear layer formed during root planing inhibits cell migration and attachment leading to impaired marginal periodontal healing. The present study was done to compare the morphological effects of root surface demineralization using citric acid and EDTA as root-conditioning agents. Materials and methods:Thirty fragments of human dental roots previously exposed to periodontal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…TC is famous for its antibacterial and anticollagenase activities. 6 At the same time, SEM images revealed an evident dissolving effect on the smear debris layer (see Fig. 10) and a sensible effect on roots' surface cuticles (see Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…TC is famous for its antibacterial and anticollagenase activities. 6 At the same time, SEM images revealed an evident dissolving effect on the smear debris layer (see Fig. 10) and a sensible effect on roots' surface cuticles (see Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, this in vitro study was designed to assess the ability of three different topicallyapplied chemicals (EDTA, TC and CA), in comparison to normal saline, to condition and biomodify the surfaces of the periodontallyaffected teeth of both healthy and diabetic patients. 6 and their existence interferes with the proper healing and attachment of perio dontal tissue. 2 This inter ference comes through limiting the intimate contact at roottissue interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated the influence of SRP combined with various conditioning agents, such as citric acid, EDTA or tetracycline hydrochlorite on smear layer removal, diameter alteration of dentinal tubules and on the dentin collagen matrix using SEM approach (16,17). These results indicate that root conditioning after SRP is favourable for smear layer removal as well as in exposing the collagen matrix (18).…”
Section: Discussionmentioning
confidence: 98%
“…Existe profusão de publicações quanto a diferentes tipos de biomodificadores radiculares químicos, sendo o ácido cítrico considerado o agente de maior efetividade na remoção da smear layer, na exposição das fibras colágenas e na abertura completa dos túbulos dentinários (MINOCHA et al, 2014, CAVASSIM et al, 2012., FONTANARI et al, 2011, AMARAL et al, 2011, PRASAD et al, 2012, ABED et al, 2013. Também tem sido demonstrado que o tratamento com ácido cítrico produz maior adesão e proliferação de fibroblastos do ligamento periodontal humano sobre as raízes (FARDAL; LOWENBERG, 1990, ROMPEN et al, 1999, assim como absorção e adesão de rede de fibrina contendo elementos celulares como eritrócitos e plaquetas, importantes para o reparo dos procedimentos cirúrgicos periodontais (AMIREDDY et al, 2011., BAKER et al, 2000…”
Section: Lista De Ilustraçõesunclassified